2005
DOI: 10.1158/0008-5472.can-03-2912
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoid X Receptor-Selective Retinoid, LGD1069, Down-regulates Cyclooxygenase-2 Expression in Human Breast Cells through Transcription Factor Crosstalk: Implications for Molecular-Based Chemoprevention

Abstract: Retinoids and their derivatives can suppress the development of cancer in animals and in humans. We and others have shown that retinoid X receptor (RXR)-selective retinoids or "rexinoids" suppress the development of breast cancer in several animal models with minimal toxicity. LGD1069 (Bexarotene) is a potent RXR-selective retinoid with reduced toxicity compared with naturally occurring retinoids. In this study, we investigated the expression of LGD1069-modulated biomarkers. We previously did cDNA array analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 26 publications
(30 reference statements)
1
44
0
3
Order By: Relevance
“…In situ hybridization A previously described method of nonradioactive in situ hybridization was used for detection of COX-2 expression (Khuri et al, 2001;Kong et al, 2005). The stained sections were reviewed in a manner similar to immunohistochemistry.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In situ hybridization A previously described method of nonradioactive in situ hybridization was used for detection of COX-2 expression (Khuri et al, 2001;Kong et al, 2005). The stained sections were reviewed in a manner similar to immunohistochemistry.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Importantly, rexinoids also exhibit preventative activity in ER-negative breast cancer experimental models, thus potentially tackling the emergence of ER-negative tumours observed in prevention trials of SERMs. In addition, rexinoids have been found to down-regulate COX-2 expression in normal mammary epithelial cells (Kong et al 2005). This finding appears of great relevance in view of the role of COX-2 in breast carcinogenesis (Dannenberg & Subbaramaiah 2003) and of the recent alerts on the risks related to the longterm use of COX-2 inhibitors in chemopreventive trials (Bresalier et al 2005, Solomon et al 2005.…”
Section: Discussionmentioning
confidence: 95%
“…It has been found that, in premalignant cells, rexinoids induce a G1 cell cycle block by inducing the expression of growth-inhibitory molecules, such as RAR-b and IGFBPs, and by suppressing the expression of growthstimulating molecules, such as cyclin D1 and COX-2 (Brown et al 2004). Kong et al (2005) have recently reported that bexarotene markedly reduces COX-2 expression in normal human mammary epithelial cells by suppression of COX-2 transcription, in part through transrepression of the AP-1 transcription factor. On the whole, these studies suggest that rexinoids are promising agents for the prevention of breast cancer and may be particularly useful in preventing the appearance of ER-negative breast tumours.…”
Section: Trials Of Novel Retinoidsmentioning
confidence: 99%
“…One of the controversies that arise regarding Targretin is the possible mechanism of action of this agent. It has been reported that Targretin can reduce the expression of COX-2 protein in normal mammary epithelium and tumors (15). The implication is that inhibition of COX-2, although perhaps indirectly, may be a significant target.…”
Section: Discussionmentioning
confidence: 99%